The Existence of a Global Attractor for the S-K-T Competition Model with Self-Diffusion - Qian Xu; Ye Zhao (Abstract and Applied Analysis)
This paper concerns the uniform bounds of the global existence of solutions in time for the S-K-T competition model with self-diffusion. We prove that the system has a global attractor for n<8.